Celostni pristop k ugotavljanju in obravnavi bolečine pri obolelih za demenco - Kobentar, Radojka (Obzornik zdravstvene nege, 2014)
Introduction: The improper treatment of pain is directly associated with the impairment of cognitive functioning, the loss of communication skills as well as the reduction of the ability to express pain. The aim of the paper is to present the scientific evidence in the field of the assessment of pain in dementia patients. Methods: Systematic review of scientific and professional literature was used, limited to publications in the English, German and Slovenian language and the publishing date (2007-2013). The selection of the results was based on the following criteria: availability, scientific basis, contextual relevance and topicality of the source. Subsequently, the data were processed with the qualitative content analysis. Results: Basic principles for the assessment and treatment of pain in people with dementia were extracted through the content analysis of 16 scientific texts. Five content categories were identified: reasons for the pain, accompanying signs, pain assessment tools, medical treatments and the role of nurses. Discussion and conclusion: It is suggested that the comprehensive approach be adopted in the assessment of pain in dementia patients within the context of behavioral problems, their functioning and living conditions. Based on the present findings it would be necessary to adopt appropriate tools for the dementia patients as a part of the quality standard treatment due to limitations in verification within clinical practice.
Keywords: bolečina; cognitive functioning; demenca; dementia; knowledge; kognitivno funkcioniranje; medical treatment; pain; zdravstvena obravnava; znanje